Literature Review Terhadap Kewajiban Moral, Kesadaran, Pengetahuan, Dimensi Keadilan, Ketegasan Sanksi Dan Pelayanan Pajak Yang Mempengaruhi Kepatuhan Pelaporan Wajib Pajak - Mhd Hasymi (JEMAP, 2022)
The literature review aims to improve the views of the previous authors and complement them with taxation practices in the field related to moral obligations, taxpayer awareness, knowledge/understanding of taxation from the taxpayer side, and from the tax authority side to determine the dimensions of tax justice, the firmness of tax sanctions and the service quality of the tax authorities towards compliance corporate taxpayer reporting. The research process includes the collectibility of published journals, identification and analysis of research results related to taxpayer compliance and other influencing factors, through Google Scholar. The results of the study are taxpayer compliance can be improved through improving information technology, the use of tax funds can be enjoyed by the wider community, involving the world of education, professional institutions, a sense of justice felt by the tax community, fair reciprocal relations between taxpayers and tax officials, availability taxpayer funds. Recommendations from the research are providing incentives (rewards) to obedient taxpayers, reducing or eliminating  multiple interpretations of the implementation of tax regulations, issuing rules that have a sense of justice and involving stakeholders from the Directorate General of Taxes.